2019
DOI: 10.9745/ghsp-d-19-00192
|View full text |Cite
|
Sign up to set email alerts
|

Provider-Initiated Family Planning Within HIV Services in Malawi: Did Policy Make It Into Practice?

Abstract: Four years after Malawi embraced a policy of provider-initiated family planning (PIFP) within its HIV Clinical Guidelines, this policy remained largely unimplemented at the health facility level. Strengthening PIFP in Malawi’s public and private health facilities will require targeted and comprehensive systems changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Similar to other African countries [50][51][52][53], there is consensus among stakeholders in Rwanda that HIV and family planning (FP) services should be integrated [54]. The Government of Rwanda strongly supports access to the full range of contraceptive options [55] and provides free therapeutic antiretrovirals (ARV) and PMTCT for HIV [56].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other African countries [50][51][52][53], there is consensus among stakeholders in Rwanda that HIV and family planning (FP) services should be integrated [54]. The Government of Rwanda strongly supports access to the full range of contraceptive options [55] and provides free therapeutic antiretrovirals (ARV) and PMTCT for HIV [56].…”
Section: Introductionmentioning
confidence: 99%
“…In summary, although Zambia has strong national policies supporting FP/HIV integration, implementation at the facility level has often been weak. 54 This study found that a systematic model for integrating FP and HIV services was associated with the increased use of effective contraception and dual method use among WLHIV in Zambia and a met need for FP. Findings from this study provide additional support for efforts to continue integrating FP and HIV services to ensure that all WLHIV have access to sexual and reproductive health services that address their fertility needs and desires.…”
Section: Discussionmentioning
confidence: 76%
“…Most often, indicators for two or more services were developed specifically for the study and measured the extent to which those services were delivered jointly. The two most common indicators were variations on (1) testing, screening, or counseling a patient with one condition for the other condition or service need [ 32 46 ]; and (2) availability of services on the same day, whether via joint treatment by the same provider or in the same visit by different providers [ 38 , 40 , 41 , 46 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other indicators included variations on (3) internal and external referral practices [ 32 , 41 , 42 , 47 ]; (4) common treatment or counseling spaces [ 41 , 47 , 50 ]; (5) availability or receipt of commodities, equipment, and or medications for two or more conditions [ 38 , 44 , 49 , 50 , 52 , 59 ]; and (6) provider knowledge on two or more services [ 35 , 39 , 52 , 55 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation